A New Tool for Collection Assessment: One Library's Response to the Calls to Action Issued by Canada's Truth and Reconciliation Commission. Issue 3 (2nd October 2017) - Linton, Janice; Ducas, Ada
ABSTRACT: The University of Manitoba's Neil John Maclean Health Sciences Library is a recognized leader in Indigenous and circumpolar health for establishing the Aboriginal Health Collection in 1997, the first discrete collection of materials on the health of Indigenous peoples located in an academic health sciences library in Canada. This article describes the history, development, and scope of what is now known as the Indigenous Health Collection. In June 2015, the Truth and Reconciliation Commission of Canada (TRC) issued the calls to action as part of its mandate to gather information and document the history of Indian Residential Schools and their legacy for all Canadians. The ninety-four calls to action provide clear guidance to governments, institutions, and people to initiate changes to address the legacy in a spirit of true reconciliation. The Neil John Maclean Health Sciences Library was uniquely positioned to respond to the TRC calls to action. The enduring legacy of the residential schools and other discriminatory government policies is one that continues to impact the health status of many people in Canada who identify as Indigenous, First Nations, Metis, Inuit, or Aboriginal. The Indigenous Health Collection includes materials on the health, wellness, and lived experience of Indigenous peoples, the determinants that impact health, and publications documenting community-based and academic research and knowledge. This article provides an example of how an academic health sciences library used the seven TRC calls to action related to health as a framework to assess the resources and collections relied on by educators and students in the health professions.